Temporal dynamics of SARS-CoV-2 antibodies and IgG subclasses following multiple doses and diverse COVID-19 vaccine combinations - Meyer, Julia; Hoerauf, Achim; Dubiel, Aleksandra Elzbieta; Kovačević, Peđa; Trudić, Anika; Primorac, Dragan; Hübner, Marc P.; Adjobimey, Tomabu; Parcina, Marijo (Frontiers in Immunology, 2026)
IntroductionDespite extensive research on COVID-19 vaccines, comparative data on the long-term humoral response across multiple vaccine platforms and heterologous regimens remain limited. SARS-CoV-2 continues to circulate and cause infections globally, highlighting the need to monitor the durability of vaccine-induced immunity. To better understand how different COVID-19 vaccination strategies shape long-term humoral immunity, we conducted a longitudinal study of the vaccines used on the European continent.MethodsThe present study investigated the humoral immune response in 331 participants between January 2021 and January 2023, who received mRNA (BNT162b2–BioNTech/Pfizer, mRNA-1273–Moderna), vector-based (ChAdOx1-S–AstraZeneca, Gam-COVID-Vac–Gamaleya Research Institute), inactivated virus (BBIBP-CorV–Sinopharm) vaccines, or a heterologous combination (ChAdOx1-S followed by mRNA), with all participants receiving an mRNA booster 6–8 months after primary vaccination. SARS-CoV-2 IgA, IgG, and IgG-subclasses were measured using ELISA, while neutralizing antibodies were assessed via a multiplex immunoassay, at four different time points: after the first and second dose, six months post-second dose and after the third dose.ResultsAfter two doses, mRNA and ChAdOx1-S-mRNA vaccination induced the highest antibody levels and neutralization potential, followed by the ChAdOx1-S and Gam-COVID-Vac vaccines. The BBIBP-CorV group showed the lowest performance. Antibody levels declined in all participants six months post-vaccination. Booster vaccination (3rd dose) induced high and comparable neutralizing antibody responses in all groups, regardless of the initial two-dose vaccine regimen. The booster vaccine induced increased SARS-CoV-2-specific IgG4 levels, particularly in participants who received two doses of mRNA-1273 as primary vaccination. The IgG subclass response was more influenced by the type of vaccine used for the two-dose primary vaccination than by the mRNA vaccine used for boosting.ConclusionAltogether, these findings underscore the importance of booster doses and provide valuable insight into the longevity and quality of humoral responses, including the durability and breadth of neutralizing antibodies, across different vaccination strategies.